2006
DOI: 10.1152/ajpheart.00831.2005
|View full text |Cite
|
Sign up to set email alerts
|

Xanthine oxidase inhibitors improve energetics and function after infarction in failing mouse hearts

Abstract: After myocardial infarction, ventricular geometry and function, as well as energy metabolism, change markedly. In nonischemic heart failure, inhibition of xanthine oxidase (XO) improves mechanoenergetic coupling by improving contractile performance relative to a reduced energetic demand. However, the metabolic and contractile effects of XO inhibitors (XOIs) have not been characterized in failing hearts after infarction. After undergoing permanent coronary ligation, mice received a XOI (allopurinol or oxypurino… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
51
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(62 citation statements)
references
References 47 publications
(78 reference statements)
10
51
1
Order By: Relevance
“…One group was untreated, the second one was treated with the general antioxidant N-acetylcysteine (NAC; 10 g/l in the drinking water), and the third group was treated with oxypurinol (OXY; an inhibitor of XO, 1 mM in the drinking water) until day 12. The concentration of oxypurinol was previously shown to inhibit XO (35). Fresh solutions were made every 48 h. On day 12, all mice were euthanized, blood was collected, and gastrocnemius muscles were removed and frozen in liquid nitrogen.…”
Section: Animalsmentioning
confidence: 99%
“…One group was untreated, the second one was treated with the general antioxidant N-acetylcysteine (NAC; 10 g/l in the drinking water), and the third group was treated with oxypurinol (OXY; an inhibitor of XO, 1 mM in the drinking water) until day 12. The concentration of oxypurinol was previously shown to inhibit XO (35). Fresh solutions were made every 48 h. On day 12, all mice were euthanized, blood was collected, and gastrocnemius muscles were removed and frozen in liquid nitrogen.…”
Section: Animalsmentioning
confidence: 99%
“…24 It is important to note, however, that in all these experimental models of heart failure, the beneficial effects of XO inhibition were achieved because XO activities were increased within the myocardium; treatment with either allopurinol or oxypurinol restored XO activity to baseline levels and myocardial function was restored. 19,21,22,[25][26][27] These findings, therefore, suggest that by limiting oxidant stress to maintain levels of ROS required for ambient signaling, XO inhibition abrogates the destructive effects of ROS on various intracellular mechanisms that maintain function and integrity in the working cardiomyocyte. In addition, it has also been suggested that decreases in uric acid levels seen with XO inhibition have an antiinflammatory effect on the cardiovascular system.…”
mentioning
confidence: 91%
“…These findings corroborate positive results seen in other studies that demonstrated improved contractile parameters in heart failure with XO inhibition. 19,21,22,[25][26][27] The positive inotropy induced by XO inhibition in the setting of heart failure differs significantly from standard clinically used pharmacological inotropes. Unlike cAMPmodulating inotropes, XO inhibition decreases myocardial oxygen consumption, thereby sparing energy expenditure in the energy-deprived failing heart.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The first is phenotyping of genetically modified mice and their wildtype controls (6 -9). The second application is characterizing the diseased heart (10 -14), sometimes combined with a study of the effects of a particular intervention (15)(16)(17)(18)(19)(20)(21). To validate the values of the MRI-based global functional parameters, several authors compare their findings with ex vivo measurements of the weight of the mouse heart (22) or to other volume measurements using, eg, positron emission tomography (23) as well as the conductance microcatheter technique (24).…”
mentioning
confidence: 99%